A strategy for screening trypsin inhibitors from traditional Chinese medicine based on a monolithic capillary immobilized enzyme reactor coupled with offline liquid chromatography and mass spectrometry. Issue 11 (24th April 2019) - Lin, Hang; Zhang, Changfa; Lin, Yuanjing; Chang, Yiqun; Crommen, Jacques; Wang, Qiqin; Jiang, Zhengjin; Guo, Jialiang
Abstract: A novel strategy was successfully developed for screening trypsin inhibitors in traditional Chinese medicines based on monolithic capillary immobilized enzyme reactors combined with liquid chromatography‐tandem mass spectrometry. Organic polymer based monolithic enzyme reactors were firstly prepared by covalently bonding trypsin to a poly(glycidyl methacrylate‐ co ‐poly (ethylene glycol) diacrylate) monolith by the ring‐opening reaction of epoxy groups. The activity and kinetic parameters of the obtained monolithic trypsin reactors were systematically evaluated using micro‐liquid chromatography. Fourier transform infrared spectroscopy and scanning electron microscopy were also used to characterize the monolithic trypsin reactors. The resulting functional and denatured monolithic trypsin reactors were applied as affinity solid‐phase extraction columns, and offline coupled with a liquid chromatography‐tandem mass spectrometry system to construct a binding affinity screening platform. Subsequently, the proposed platform was applied for screening trypsin binders in a Scutellaria baicalensis Georgi extract. Three compounds, namely scutellarin, baicalin, and wogonoside were identified, and their inhibitory activities were further confirmed via an in vitro enzymatic inhibition assay. Additionally, molecular docking was also performed to study the interactions between trypsin and these three compounds.